1970
DOI: 10.2134/agronj1970.00021962006200040011x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Time of Harvest and Nitrogen Level on Yield and Grain Breakage in Transplanted Rice1

Abstract: An application of up to 120 kg/ha of nitrogen fertilizer in the dry season improved the milling quality of the chalky varieties ‘IR8,’ ‘IR5,’ and ‘Sigadis’ but not that of the nonchalky variety ‘C4‐63.’ An application of up to 60 kg/ha of nitrogen increased the protein content of brown rice of the four varieties but increased the head rice yield of only Sigadis, the most chalky of the four varieties; the head rice yield of the other three varieties remained unchanged. Irrespective of variety and nitrogen level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 1 publication
8
40
0
1
Order By: Relevance
“…Early work with improved rice varieties conducted in the 1960s and 1970s demonstrated that grain protein could be significantly increased by ensuring adequate nitrogen fertilizer application up to panicle initiation stage (Nangju and De Datta, 1970;De Datta et al, 1972). Subsequent field research has found that improved fertilizer nitrogen use efficiency to achieve both high yields and high grain quality requires careful attention to the rate and timing of nitrogen fertilizer applications such that the total available nitrogen supply from soil and fertilizer is congruent with crop nitrogen demand.…”
Section: Ricementioning
confidence: 99%
“…Early work with improved rice varieties conducted in the 1960s and 1970s demonstrated that grain protein could be significantly increased by ensuring adequate nitrogen fertilizer application up to panicle initiation stage (Nangju and De Datta, 1970;De Datta et al, 1972). Subsequent field research has found that improved fertilizer nitrogen use efficiency to achieve both high yields and high grain quality requires careful attention to the rate and timing of nitrogen fertilizer applications such that the total available nitrogen supply from soil and fertilizer is congruent with crop nitrogen demand.…”
Section: Ricementioning
confidence: 99%
“…Certain physiological and chemical factors involved in the maturity, grain hardness and cracking have also been recorded (Nagato and Kono 1963;Nangju and De Datta 1976;Bhashyam et al 1985;Srinivas et a1 1985). Although the varietal and genetic bases of grain cracking (Srinivas et al 1977;Kunze and Prasad 1978) and of plant and panicle characters in relation to yield (Mallik et a1 1988a b; Bashar et a1 1991, Anon 1991) have been independently studied, it has not been possible to assign a discrete phenotype to the unique cracking character to show its relation with plant and panicle morphology.…”
Section: Introductionmentioning
confidence: 92%
“…The current hypothesis is that yield is related to the nitrogen-supplying capacity of the soil, which in turn determines the grain protein content (Perez et al, 1996). The application of nitrogen fertilizer at different stages, from panicle initiation to flowering and the grain-filling stages, significantly increases the seed-storage protein content (Nangju and De Datta, 1970;Taira et al, 1970;Nagarajah et al, 1975). It also improves protein content-related traits such as the growth rate of milled and head rice (Wopereis-Pura et al, 2002;Leesawatwong et al, 2005), and translucency (Perez et al, 1990).…”
Section: Fertilizermentioning
confidence: 99%